Implementasi Algoritma FIFO (First In First Out) Pada Sistem Pergudangan Di Bagian Furniture Production - Muhammad Ruslan Maulani; Supriady; Marwanto Rahmatuloh; Indah Triapriliani; Hafidzul Fauzan (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
CV Manis Maqbul Jaya is a Specialist Interior Design company, Furniture Production, Contractor Consultant and Kitchen Set Design. In the warehousing process carried out by CV Manis Maqbul Jaya, they still use the manual method, namely the process of goods entering the warehouse and the process of goods leaving the warehouse by recording using a book. Warehousing is used for the storage of goods, namely raw materials and finished goods (Production). The recording of manual inventory updates causes the accumulation of transaction data for incoming and outgoing goods, due to delays in delivering information from store clerks and production officers to warehouse officers or vice versa. so that the process of releasing goods is carried out not based on storage or expiration dates, resulting in damaged or expired old goods. These problems can be overcome by creating a warehousing application using the FIFO (First in First Out) method, where the first item that enters means that the item is the first one out. The warehouse application is software that functions to record and monitor all activities of goods leaving the warehouse and entering the warehouse in real-time. This application is made on a web-based basis to assist the process of recording inventory updates, accurate goods data can be used as an evaluation of incoming goods as an inventory report, thus facilitating the process of running calculations in inventory recording by paying attention to the quality of wood and the expiration of goods used in the warehousing process.